Uniqueness of Solutions of Some Nonlocal Boundary-Value Problems for Operator-Differential Equations on a Finite Segment - Radzievskii, G.V. (Український математичний журнал, 2003)
For the equation L₀x(t) + L₁x⁽¹⁾(t) + ... + Lnx⁽ⁿ⁾(t) = 0, where Lk, k = 0, 1, ... , n, are operators acting in a Banach space, we formulate conditions under which a solution x(t) that satisfies some nonlocal homogeneous boundary conditions is equal to zero.